Meet European Society for Research in Mathematics Education (ERME) - Novotná, Jarmila; Stehlíková, Naďa (Scientia in educatione, 2020)
The article concerns the European organisation of ERME which was founded in 1997 with the goal to map and to a certain extent coordinate European research in mathematics education. The Czech researchers have been active in this organisation since its very beginning. Scientific conferences and activities for young researchers which are organised by the Society are described in more detail.